Muslim Consumer Preferences for Halal Food Products: The Role of Halal Labels, Product Quality and Socio-Cultural Factors - Nadia Yupita Sari; Eka Sri Wahyuni; Khozin Zaki (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the influence of halal labels, product quality, and socio-cultural factors on Muslim consumer preferences for Nissin Gekikara Ramen products in Bengkulu City. Amid the rapid growth of the halal market, global food products face challenges in balancing international quality standards with religious adherence. This study used a quantitative approach with a survey method of 120 Muslim respondents selected through a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results show that product quality and socio-cultural factors have a positive and significant influence on consumer preferences, with socio-cultural factors being the most dominant factor. In contrast, the halal label has no significant influence, indicating a shift where the halal label on global brands is now considered a basic standard (basic requirement) rather than a primary attraction. The novelty of this study lies in the integration of the sharia consumption perspective with local socio-cultural dynamics that go beyond religious formalities. These findings provide important implications for manufacturers to emphasize cultural relevance and functional quality in winning the Muslim market in Indonesia.